Penerapan Google Earth Dalam Pembelajaran Geografi Untuk Meningkatkan Hasil Belajar Siswa Di SMA Negeri 1 Tilango - Yusuf, Andrianto; Rusiyah, Rusiyah; Pratama, M. Iqbal Liayong (Universitas Negeri Gorontalo, 2024)
Behavioral changes brought about by the learning process are called learning outcomes. By utilizing Google Earth multimedia about Indonesian flora and fauna, this research seeks to improve the learning outcomes of class XI students. This research uses a Classroom Action Research (PTK) design. The main goal of PTK is to help teachers solve learning challenges in the classroom and to improve and improve the quality of learning. SMA Negeri 1 Tilango, Gorontalo Regency, Gorontalo Province was the location for this research. The research was conducted in 2024 between June and July. Class XI students were used as research subjects. The instruments of this research are test questions, teacher activity observation sheets, and student activity observation sheets. The research results showed that the learning management activities observed by teachers in Cycle I were in the best condition with a percentage value of 44.4%; in Cycle II it increased to a maximum of 55.6%; and in the maximum category it reaches 100%. Student activities in cycle I produced 66.7% very good learning aspects, 16.7% good learning aspects, and 16.7% negative learning aspects. In contrast, the second cycle student activity score showed 16.7% in the good category and 83.3% in the very good category. Utilizing Google Form as a tool for monitoring student learning outcomes, student learning outcomes are processed in cycles I and II. Completeness of student learning outcomes in cycle I was 53.33% and incomplete student learning outcomes was 46.67%. These results are based on observations made by observers. On the other hand, 87.88% of students completed cycle II, and 12.12% of students showed incomplete results. Based on the research results, the learning outcomes of class XI IPS 3 students at SMA Negeri 1 Tilango regarding the distribution of flora and fauna can be improved by using Google Earth media.